2001
DOI: 10.1046/j.1365-2133.2001.04133.x
|View full text |Cite
|
Sign up to set email alerts
|

First experience of topical SDZ ASM 981 in children with atopic dermatitis

Abstract: In these children 1-4 years of age, blood concentrations of SDZ ASM 981 during topical treatment with the 1% cream were consistently low even in the children with the most extensive areas treated (up to 69% of their BSA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
110
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 7 publications
(10 reference statements)
5
110
0
6
Order By: Relevance
“…20,27,[30][31][32]44 The favorable safety and tolerability profile of 1% pimecrolimus cream demonstrated in published pediatric studies 35,[37][38][39]43,44 is supported by the data summarized in this review. The combined analysis of the results from 4 pharmacokinetic studies conducted with 35 infants with AD indicated that pimecrolimus blood concentrations after topical applications were consistently low, irrespective of the level of disease severity and percentage of TBSA involved.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…20,27,[30][31][32]44 The favorable safety and tolerability profile of 1% pimecrolimus cream demonstrated in published pediatric studies 35,[37][38][39]43,44 is supported by the data summarized in this review. The combined analysis of the results from 4 pharmacokinetic studies conducted with 35 infants with AD indicated that pimecrolimus blood concentrations after topical applications were consistently low, irrespective of the level of disease severity and percentage of TBSA involved.…”
Section: Discussionmentioning
confidence: 74%
“…As shown in pediatric and adult pharmacokinetic studies, blood concentrations after treatment with pimecrolimus cream are very low or undetectable. 30,43,44 Blood concentrations display similar low values 2, 4, 6, and 12 hours after application, with no peak. Concentration ranges are similar on days 4 and 22, which indicates no systemic accumulation of pimecrolimus after topical application.…”
mentioning
confidence: 84%
See 3 more Smart Citations